Phraseological units with a component "bird" in the Mordovian and Finnish languages (semantic analysis) - Natalya M. Mosina (Publishing house "Sreda", 2023)
The purpose of the study is to identify common and distinctive features of Mordovian and Finnish phraseological units with the zoonym component "bird". The relevance of this study is due to the need for a comprehensive study of phraseological units in order to identify common and specific features inherent in these linguistic cultures. The object of the study was the phraseological units of the Mordovian and Finnish languages, in which the zoonym component "bird" was identified. Based on the methods of descriptive, comparative, component analysis, the semantic characteristics of phraseological units are studied, dominant images are identified, universal phenomena and distinctive features in the meanings conveyed by phraseological units in the compared languages are determined. The main material of the study is presented by phraseological units with a zoocomponent, identified by continuous sampling from explanatory monolingual and bilingual dictionaries, as well as phraseological developments, texts of fiction and journalistic literature. The properties that the Mordovians and Finns attribute to poultry are in most cases similar, which is why both languages have a lot of phraseological units that coincide in meaning. In both Mordovian and Finnish cultures, the bird is considered a creature that is not very smart. The observed phenomenon is to a greater extent associated with domestic poultry, and to a lesser extent with wild birds.